Economic assessment of renovation , replacement and cocnstruction of water supply networks in the excavation or with selected trenchless methods - Szymoniak, Aleksander; Piechurski, Florian (Instal, 2021)
The aim of the work was to evaluate the economic use of trenchless and excavation technologies in construction renovation and replacement of water supply networks. Three actually implemented investments in the R city were used to carry out the assessment. Based on these investments, cost estimates were prepared for each of the trenchless methods. Then each was compared from trenchless methods with the open excavation method. After analyzing the data, it was found that the selected trenchless methods are more advantageous in terms of economy and speed of investment implementation compared to the open excavation method.